Earth's Climate Sensitivity: Apparent Inconsistencies in Recent Assessments. (8th December 2014) - Schwartz, Stephen E.; Charlson, Robert J.; Kahn, Ralph; Rodhe, Henning
Abstract Earth's equilibrium climate sensitivity (ECS) and forcing of Earth's climate system over the industrial era have been re‐examined in two new assessments: the Fifth Assessment Report (AR5) of the Intergovernmental Panel on Climate Change (IPCC), and a study by Otto et al. (2013). The ranges of these quantities given in these assessments and also in the Fourth (2007) IPCC Assessment are analyzed here within the framework of a planetary energy balance model, taking into account the observed increase in global mean surface temperature over the instrumental record together with best estimates of the rate of increase of planetary heat content. This analysis shows systematic differences among the several assessments and apparent inconsistencies within individual assessments. Importantly, the likely range of ECS to doubled CO2 given in AR5, 1.5–4.5 K/(3.7 W m−2) exceeds the range inferred from the assessed likely range of forcing, 1.2–2.9 K/(3.7 W m−2), where 3.7 W m−2 denotes the forcing for doubled CO2. Such differences underscore the need to identify their causes and reduce the underlying uncertainties. Explanations might involve underestimated negative aerosol forcing, overestimated total forcing, overestimated climate sensitivity, poorly constrained ocean heating, limitations of the energy balance model, or a combination of effects.